2018
DOI: 10.3389/fimmu.2018.00144
|View full text |Cite
|
Sign up to set email alerts
|

Blood CXCR3+ CD4 T Cells Are Enriched in Inducible Replication Competent HIV in Aviremic Antiretroviral Therapy-Treated Individuals

Abstract: We recently demonstrated that lymph nodes (LNs) PD-1+/T follicular helper (Tfh) cells from antiretroviral therapy (ART)-treated HIV-infected individuals were enriched in cells containing replication competent virus. However, the distribution of cells containing inducible replication competent virus has been only partially elucidated in blood memory CD4 T-cell populations including the Tfh cell counterpart circulating in blood (cTfh). In this context, we have investigated the distribution of (1) total HIV-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…These cells are characterized by surface expression of CXCR5 and PD-1, reside in the lymph node follicles in immediate anatomical proximity to B cells, and support the germinal center reaction essential for the generation of effective humoral immunity. Notably, the group of Matthieu Perreau, by investigating lymph node T fh (expressing CXCR5 and PD-1) and pT fh (expressing CXCR3), has shown that these subpopulations are the major sources of infectious replication-competent HIV-1 (Banga et al, 2016b(Banga et al, , 2018.…”
Section: Cd4 + T Cell Functional Subsetsmentioning
confidence: 99%
“…These cells are characterized by surface expression of CXCR5 and PD-1, reside in the lymph node follicles in immediate anatomical proximity to B cells, and support the germinal center reaction essential for the generation of effective humoral immunity. Notably, the group of Matthieu Perreau, by investigating lymph node T fh (expressing CXCR5 and PD-1) and pT fh (expressing CXCR3), has shown that these subpopulations are the major sources of infectious replication-competent HIV-1 (Banga et al, 2016b(Banga et al, , 2018.…”
Section: Cd4 + T Cell Functional Subsetsmentioning
confidence: 99%
“…Although different CD4+ T cell subsets have been identified as major contributors to the HIV-1 reservoir (Chomont et al, 2009;Hiener et al, 2017;Lee et al, 2017b) and different surface markers (CXCR3, CD30, and CD32a) (Banga et al, 2018;Descours et al, 2017;Henrich et al, 2017) and immune exhaustion markers (PD-1, TIGIT, and LAG-3) (Khoury et al, 2017;McGary et al, 2017) have emerged as potential biomarkers for latently infected cells, previous studies have not converged on a clear pattern or predominant subsets responsible for HIV persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Various differentiation states of CD4 T cells appear to play important roles in the establishment and maintenance of the LR as well as viral recrudescence following ART interruption (Buzon et al, 2014;Kulpa and Chomont, 2015;Banga et al, 2016;De Scheerder et al, 2019;Falcinelli et al, 2019). As discussed above, the LR is primarily hosted in memory CD4 T cells, specifically, central (T CM ), transitional (T TM ), effector memory (T EM ), and memory stem (T SCM ) cells, although the exact contribution of each cell type to the replication competent reservoir is still to be determined (Chomont et al, 2009;Buzon et al, 2014;Soriano-Sarabia et al, 2014;Banga et al, 2016Banga et al, , 2018Kwon et al, 2020). Recently, CD32+ CD4 T cells have been proposed to be a major host of the LR, whereby selection of this cell population resulted in significant enrichment of inducible provirus (Descours et al, 2017;Darcis et al, 2020).…”
Section: The Hosts Of the Reservoirmentioning
confidence: 99%